Assessment of tracheobronchial and lung dose due to radon and thoron inhalation - Shatha Farhan Alhous; Ansam Fadil Showard; Shaymaa Awad Kadhim (Journal of the Pakistan Medical Association)
The main sources of natural background radiation are radon, thoron and their progeny, which may cause health risks to humans. Keeping in mind the importance of the subject, three samples each from 10 selected residential areas, including the centre of Babylon Governorate, Iraq, and its districts, were collected. Concentration of radon and thoron was measured using solid-state track detectors (CR-39). The arithmetic means of the concentration of radon and thoron were 47.367±19.56 and 133.246±16.585 Bqm-3, respectively; these values are considered safe when compared with the upper reference level of 200-600 Bqm-3 recommended by the International Commission for Radiological Protection (ICRP). The value of the inhalation equivalent dose from radon gas discovered in these areas with rate 37.893 nSv is less than the value of the global average of 1.15 mSv. This indicates that the risks related to inhalation of radon are low as the lung dose rate (DLung), tracheobronchial region (DT-B), annual effective dose (AED) and excess lifetime cancer risk (ELCR) is (1.894 nGyh-1, 22.736 nSv, 0.236 mSvy-1 and 0.835 x10-3), respectively. While the value of the inhalation equivalent dose (IED) from thoron as effective dose to lung DLung, AED and ELCR are equal to (0.133 nSv, 0.167 mSvy-1 and 0.587 x 10-3), respectively. To conclude, the rates in the study area are less than the ICRP recommended level of 3 mSv; therefore, the studied areas are safe from the health risks of inhalation of radon and thoron. Key Words: Radiation, Radon, Lung,